Управління міграційними процесами в контексті європейської інтеграції України - Shcherbakova, Olena A.; Stepaniuk, Yevhen V. (Institute of Industrial Economics of NAS of Ukraine, 2025)
The key trends and challenges of global migration processes are synthesized with a focus on the implications of a full-scale war in Ukraine. The structure of the European Union's economy and demographic trends in Europe are analyzed from the perspective of Ukraine's European integration and the creation of a common labor market. Based on the results of the study, the authors conclude that in order to regulate migration processes and preserve the competitiveness of the national economy, a long-term, coordinated and evidence-based policy is needed. It should be aimed at facilitation of cross-border movement of human capital, which will help maximize the overall benefits of migration, starting from the development of trade and investment ties to increased productivity, skills transfer and poverty reduction. Given that in the medium term Ukraine, especially in view of its EU accession prospects, is likely to act as a transit hub for migration flows, serving both as a country of origin and a country of destination of migrants, the authors propose state policy measures to manage migration processes and migrant integration. This includes the creation of a system for monitoring migration flows, measures to improve the efficiency of the labor market and the quality of public sector services, improving the business environment, professional training programs, certification of skills, consultative support, mobility of social benefits and development of capital markets. The authors emphasize the expediency of developing a comprehensive migration policy in Ukraine aimed at attracting foreign workers, supporting the reintegration and return of highly skilled migrants, including through programs for the diaspora. The authors analyze the prospects for further cooperation between Ukraine and EU countries in creating a legal framework for legal migration to provide mobility pathways for Ukrainians after the war, including partnerships on skills mobility. In their opinion, the implementation of a comprehensive policy of migration and reintegration of migrants should balance the supply and demand of skilled labor in the industrial sector of Ukraine. The language of the article is Ukrainian.